2021
DOI: 10.1186/s40364-021-00342-4
|View full text |Cite
|
Sign up to set email alerts
|

Nucleases as molecular targets for cancer diagnosis

Abstract: Early cancer diagnosis is a crucial element to improved treatment options and survival. Great research efforts have been made in the search for better performing cancer diagnostic biomarkers. However, the quest continues as novel biomarkers with high accuracy for an early diagnosis remain an unmet clinical need. Nucleases, which are enzymes capable of cleaving nucleic acids, have been long considered as potential cancer biomarkers. The implications of nucleases are key for biological functions, their presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 86 publications
(204 reference statements)
0
28
0
Order By: Relevance
“…DNA exonucleases may favour the appearance of mutations in healthy cells, converting them into tumour cells, or may be necessary for certain tumours to keep the inherent genomic instability of malignancy under control, aiding tumour cells to avoid cell death, or impact on the immune response. In this manner, aberrant DNAse activity in tumours have been suggested to be exploited as a molecular whistleblower for diagnosis [ 246 ]. Hence, these types of enzymes are promising targets for cancer treatment promoting synthetic lethality and early detection of certain types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DNA exonucleases may favour the appearance of mutations in healthy cells, converting them into tumour cells, or may be necessary for certain tumours to keep the inherent genomic instability of malignancy under control, aiding tumour cells to avoid cell death, or impact on the immune response. In this manner, aberrant DNAse activity in tumours have been suggested to be exploited as a molecular whistleblower for diagnosis [ 246 ]. Hence, these types of enzymes are promising targets for cancer treatment promoting synthetic lethality and early detection of certain types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers could be molecular, physiologic, histologic, or radiographic [148]. In this regard, many nucleases have been the topic of research that indicated their potential utility as diagnostic biomarkers for various cancer types such as prostate cancer [54], gynecologic cancers [149,150], breast [151,152], head and neck squamous cell carcinoma (HNSCC) [17], colorectal [153] and others as reviewed in paper I [36].…”
Section: Nucleases As Potential Biomarkers In Cancer Diagnosismentioning
confidence: 99%
“…Moreover, nucleases are naturally occurring enzymes in all of the three domains of life: Bacteria, Archaea, and Eukarya [22][23][24], as intracellular [25], membrane bound [25,26] or secreted proteins [3]. The diversity of these enzymes encouraged implementation in wide applications, as tools in nucleic acid bioengineering [27], therapeutic molecular targets [28][29][30][31][32][33][34], therapeutic agents [2,25,35], and as disease biomarkers [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is a threat to human health worldwide owing to the high morbidity and mortality rates. All cancer cells are characterized by common hallmarks, including transformation, unrestricted growth, and progression [ 7 10 ]. Various factors have been identified that contribute to cancer initiation and progression, including gene mutations, suppressed immune responses, and a complex tumor microenvironment (TME) [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%